2001
DOI: 10.1530/eje.0.1450749
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in features associated with polycystic ovary syndrome in normogonadotrophic oligo-amenorrhoeic infertile women of reproductive years

Abstract: Objective: To assess the effect of age on clinical, endocrine and sonographic features associated with polycystic ovary syndrome (PCOS) in normogonadotrophic anovulatory infertile women of reproductive years. Design: Cross-sectional study. Methods: Four hundred and seventy-two oligo-amenorrhoeic infertile patients, presenting with normal FSH and oestradiol concentrations, aged 17±42 years underwent a standardised initial evaluation including: cycle history, body mass index, waist-to-hip ratio and transvaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 41 publications
8
42
2
2
Order By: Relevance
“…Additionally, in either pre-or postmenopausal normal women, a direct relationship between androgen levels and IR or DM risk has been determined (40,41). In women with PCOS, but also in controls, androgen levels gradually decrease through time, as has been shown in several studies (42,43,44,45) and confirmed in the present one. However, it should be emphasized that androgens decreased irrespective of the BMI, implying that the association of androgens with age is direct and not through obesity.…”
Section: Figuresupporting
confidence: 82%
“…Additionally, in either pre-or postmenopausal normal women, a direct relationship between androgen levels and IR or DM risk has been determined (40,41). In women with PCOS, but also in controls, androgen levels gradually decrease through time, as has been shown in several studies (42,43,44,45) and confirmed in the present one. However, it should be emphasized that androgens decreased irrespective of the BMI, implying that the association of androgens with age is direct and not through obesity.…”
Section: Figuresupporting
confidence: 82%
“…Hence, increased intraovarian AMH production in PCOs may slow down the process of primordial follicle recruitment and thus retard depletion of the primordial follicle pool. Although it has been reported that cycle irregularities and hormonal profiles improve with increasing age (37)(38)(39), data regarding the age of menopause in these women are lacking. However, menopausal age in these women is difficult to establish because most of them will regulate their cycles up to advanced age using oral contraceptive pills.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that androgen secretion spontaneously decreases after the age of 35 in normal and PCOS women (34,35) and that in the general population the prevalence of polycystic ovaries appears to decrease with age too (36). Further, women with polycystic ovaries may regain normal menses with age (37) and may also get spontaneous fertility (38).…”
Section: Changes In Polycystic Ovaries and Androgens With Agementioning
confidence: 99%